Energy balance at high altitude - Westerterp, Klaas R.; Kayser, Beng; Wouters, Loek; Le Trong, Jean Louis; Richalet, Jean Paul (Acta Andina, 2025)
Weight loss, due to malnutrition and possibly intestinal malabsortion, is a well know phenomenon in high altitude climbers. Up to ~ 5000 m energy balance may be attained and intestinal energy digestibility remains normal. In order to see whether 1) energy digestibility would play a significant role in the energy deficit, energy digestibility would play a significant role in the energy deficit, energy intake, energy expenditure, body composition and energy digestibility of 10 subjects (four women and six men , 27-44 yr) were assessed during a 21 day sojourn on the summit of Mt. Sejama, Bolivia (6542 m). Energy intake was measured during two 3 day intervals: 7-9 (EI1) and I 7-19 (EI2). Total fecal loss during EI1, was calculated from fecal energy measured by bomb calorimetry. Average daily metabolic rate (ADMR) at altitude was measured in six subjects, two women and four men, with doubly labeled water over a 10 day interval: 9- 19. Basal metabolic rate (BMR) was measured before and after the expedition by respiratory gas analysis. Body composition was estimated from skinfolds and body mass before and during the altitude sojourn. Subjects were in negative energy balance throughout the observation period (EI - ADMR = -2.9 ± 1.8 MJ/d and EI2 - ADMR = -2.3 ± 1.8 MJ/d,based on a gross energy digestibility of 95%). The loss of fat mass (3.7 ± 1.5 Kg) represented 74 ± 15% of the loss of body mass. Energy content of the feces was 21 KJ/d dry weight and gross energy digestibility amounted 85%. The energy deficit increased to 3.5 MJ/d after correction for the decreased energy digestibility. In conclusion, energy balance was not attained at 6542 m. The resulting energy deficit appeared to result mosțly from malnutrition and only a limited part could be attributed to malabsorption.